2023
DOI: 10.2147/dddt.s405266
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate Attenuates Renal Tubular Cell Apoptosis by Up-Regulating MCAD in Diabetic Kidney Disease

Abstract: Background Diabetic kidney disease (DKD) is a major diabetic microvascular complication. Fatty acid-induced lipotoxicity and apoptosis were associated with the exacerbation of DKD. However, the association of lipotoxicity with renal tubular apoptosis and the effects of fenofibrate on DKD are not fully understood. Methods Eight-week-old db/db mice were given fenofibrate or saline by gavage for 8 weeks. Human kidney proximal tubular epithelial (HK2) cells stimulated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…29 Our study found that TG was one of the predictors for DKD, consistent with the conclusion of previous studies. 30 The studies 31,34 found that at least eight standard predictors, such as eGFR, urinary albumin, SCR, T1DM disease course, HbA1c, age, and BMI, effectively indicated that Cys-C, renal resistance index, and renal injury molecular-1 may be related to the risk of DKD, which confirmed the potential value of Cys-C in predicting the risk of developing DKD in patients with T1DM. The results of this study showed that patients with higher Cys-C had a significantly increased risk of DKD, and subsequent analyses found that Cys-C could be used to predict the occurrence of DKD.…”
mentioning
confidence: 86%
“…29 Our study found that TG was one of the predictors for DKD, consistent with the conclusion of previous studies. 30 The studies 31,34 found that at least eight standard predictors, such as eGFR, urinary albumin, SCR, T1DM disease course, HbA1c, age, and BMI, effectively indicated that Cys-C, renal resistance index, and renal injury molecular-1 may be related to the risk of DKD, which confirmed the potential value of Cys-C in predicting the risk of developing DKD in patients with T1DM. The results of this study showed that patients with higher Cys-C had a significantly increased risk of DKD, and subsequent analyses found that Cys-C could be used to predict the occurrence of DKD.…”
mentioning
confidence: 86%
“…Fenofibrate decreased TG content and lipid accumulation in DKD and increased activation of the AMPK/FOXA2/medium-chain acyl-CoA dehydrogenase pathway, significantly reducing renal function and tubular cell apoptosis and slowing DKD progression ( 186 ).…”
Section: Targeting Lipid Metabolism For Dkd Treatmentmentioning
confidence: 99%